Cluster Observations with the South Pole Telescope - Plagge, Thomas Jeffrey (eScholarship, University of California, 2009)
The South Pole Telescope (SPT) is an instrument designed to survey galaxy clusters using the Sunyaev-Zel'dovich effect. In this thesis I describe the telescope, its first-generation receiver, and its readout and control systems. I also present Sunyaev-Zel'dovich measurements of 15 massive X-ray selected galaxy clusters obtained with the SPT. The cluster signals are measured at 150 GHz, and concurrent 220 GHz data are used to reduce astrophysical contamination. Radial profiles are computed using a technique that takes into account the effects of the beams and filtering. In several clusters, significant SZ decrements are detected out to a substantial fraction of the virial radius. The profiles are fit to the -model and to a generalized NFW pressure profile, and are scaled and stacked to probe their average behavior. The best-fit model parameters are consistent with previous studies: β = 0.86 and r core /r 500 = 0.20 for the β-model, and (α, β, γ, c 500 )=(1.0, 5.5, 0.5, 1.0) for the generalized NFW model. Both models fit the SPT data comparably well, and both are consistent with the average SZ profile out to the virial radius. The integrated Compton-y parameter Y SZ is computed for each cluster using both model-dependent and model-independent techniques, and the results are compared to X-ray estimates of cluster parameters. Y SZ is found to scale with Y X and gas mass with low scatter. Since these observables have been found to scale with total mass, these results point to a tight mass-observable relation for the SPT cluster survey.